Geographic variation and trade‐offs in parasitoid virulence. (12th September 2016) - Fors, Lisa; Markus, Robert; Theopold, Ulrich; Ericson, Lars; Hambäck, Peter A.
Summary: Host–parasitoid systems are characterized by a continuous development of new defence strategies in hosts and counter‐defence mechanisms in parasitoids. This co‐evolutionary arms race makes host–parasitoid systems excellent for understanding trade‐offs in host use caused by evolutionary changes in host immune responses and parasitoid virulence. However, knowledge obtained from natural host–parasitoid systems on such trade‐offs is still limited. In this study, the aim was to examine trade‐offs in parasitoid virulence in Asecodes parviclava (Hymenoptera: Eulophidae) when attacking three closely related beetles: Galerucella pusilla, Galerucella calmariensis and Galerucella tenella (Coleoptera: Chrysomelidae). A second aim was to examine whether geographic variation in parasitoid infectivity or host immune response could explain differences in parasitism rate between northern and southern sites. More specifically, we wanted to examine whether the capacity to infect host larvae differed depending on the previous host species of the parasitoids and if such differences were connected to differences in the induction of host immune systems. This was achieved by combining controlled parasitism experiments with cytological studies of infected larvae. Our results reveal that parasitism success in A. parviclava differs both depending on previous and current host species, with a higher virulence when attacking larvae of the same species as the previous host. Virulence was in general high for parasitoids from G. pusilla and low for parasitoids from G. calmariensis . At the same time, G. pusilla larvae had the strongest immune response and G. calmariensis the weakest. These observations were linked to changes in the larval hemocyte composition, showing changes in cell types important for the encapsulation process in individuals infected by more or less virulent parasitoids. These findings suggest ongoing evolution in parasitoid virulence and host immune response, making the system a strong candidate for further studies on host race formation and speciation. Abstract : This study examines trade‐offs in parasitoid virulence in a hymenopteran attacking three closely related beetles, revealing a higher parasitism success when infecting larvae of the same species as the previous host. These observations are linked to changes in the larval hemocyte composition when infected by more or less virulent parasitoids.